DEFECT PRODUCT COMPARISON OF THE USE OF ALCOHOL-BASED FOUNTAIN SOLUTION AND ALCOHOL-FREE IN OFFSET PRINTING - Mawan Nugraha; Murdani Murdani (Politeknik Negeri Media Kreatif, 2020)
One of the main components of the fountain solution used for the offset printing technique is isoprophil alcohol (IPA), which is related to its function as a surface tension reducing agent, cooling agent for printing plates and at the same time having anti-bioorganic function. However, complaints have also been made about the weaknesses in the use of IPA related to odor, toxicity and too high evaporation rate during its use. Therefore, in this article, IPA is compared to the